2021
DOI: 10.1242/dev.199814
|View full text |Cite
|
Sign up to set email alerts
|

Signalling pathways and transcriptional regulators orchestrating liver development and cancer

Abstract: Liver development is controlled by key signals and transcription factors that drive cell proliferation, migration, differentiation and functional maturation. In the adult liver, cell maturity can be perturbed by genetic and environmental factors that disrupt hepatic identity and function. Developmental signals and fetal genetic programmes are often dysregulated or reactivated, leading to dedifferentiation and disease. Here, we highlight signalling pathways and transcriptional regulators that drive liver cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 122 publications
0
17
0
Order By: Relevance
“…During embryonic development liver organogenesis arises from the foregut endoderm, a region from which pancreas progenitors are also derived. Signals from adjacent cardiac mesoderm and the septum transversum mesenchyme (STM), particularly fibroblast growth factor (FGF) and bone morphogenic protein (BMP) respectively, suppress the pancreas program and, together with Nodal signalling, specify the hepatic fate with the emergence of hepatoblasts, the liver parenchymal progenitor cells [2,8]. The expansion of the hepatoblast pool is to a great extent regulated by BMP, FGF, WNT and transforming growth factor  (TGF) signalling from the nearby endothelium and the STM [8].…”
Section: Cellular Signals and Pioneer And Non-pioneer Transcription F...mentioning
confidence: 99%
See 1 more Smart Citation
“…During embryonic development liver organogenesis arises from the foregut endoderm, a region from which pancreas progenitors are also derived. Signals from adjacent cardiac mesoderm and the septum transversum mesenchyme (STM), particularly fibroblast growth factor (FGF) and bone morphogenic protein (BMP) respectively, suppress the pancreas program and, together with Nodal signalling, specify the hepatic fate with the emergence of hepatoblasts, the liver parenchymal progenitor cells [2,8]. The expansion of the hepatoblast pool is to a great extent regulated by BMP, FGF, WNT and transforming growth factor  (TGF) signalling from the nearby endothelium and the STM [8].…”
Section: Cellular Signals and Pioneer And Non-pioneer Transcription F...mentioning
confidence: 99%
“…This gene expression signature is progressively established from early hepatic development through cell-to-cell signalling and a network of key transcription factors (TFs) and their activation or repression complexes, that shape up liver-specific gene expression [6]. After birth, an increasingly complex set of cross-regulated TFs, plus signalling systems such as WNT and Notch, and splicing regulators (SR), define the liver zonal architecture and consolidate mature hepatocellular function [2,[6][7][8]]. An intricate system of signals, TFs and epigenetic mechanisms secure the preservation of the liverspecific gene expression pattern (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…During the subsequent growth phase, the size, shape, and placement of liver began to extend across the midline ventral to esophagus and forms the architecture [ 54 ]. Studies in mammals indicated that liver development began with the appearance of liver buds, to the formation of liver progenitor cells, followed by the proliferation, differentiation, and migration of hepatic progenitor cells, and finally to the formation of liver, undergoing a complex process of cell signal regulation [ 12 , 21 , 53 ]. Furthermore, extrinsic signaling pathways and cell-autonomous transcription factors tightly regulate liver organogenesis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The liver development process involved in many pathways, such as bone morphogenetic protein (BMP), transforming growth factor β (TGFβ), Wnt, and Hippo and Notch signaling pathways in mammals [ 21 ]. The Wnt signaling pathway tightly controls embryogenesis, including hepatobiliary development, maturation, and zonation, and it can increase glucose metabolism in hepatocellular carcinoma cells [ 12 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation